2010
DOI: 10.1515/znc-2010-1-213
|View full text |Cite
|
Sign up to set email alerts
|

Difference of Physiological Characters in Dark Green Islands and Yellow Leaf Tissue of Cucumber mosaic Virus (CMV)-Infected Nicotiana tabacum Leaves

Abstract: Dark green islands (DGIs) are a common symptom of plants systemically infected with the mosaic virus. DGIs are clusters of green leaf cells that are free of virus but surrounded by yellow leaf tissue that is full of virus particles. In Cucumber mosaic virus (CMV)-infected Nicotiana tabacum leaves, the respiration and photosynthesis capabilities of DGIs and yellow leaf tissues were measured. The results showed that the cyanide-resistant respiration was enhanced in yellow leaf tissue and the photosynthesis was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…First, a cause-and-effect relationship between animal phagocytosis and the accumulation of ROS has been demonstrated (Morel et al 1991;Segal 2008). Second, ROS accumulation has been also associated and functionally linked to numerous plant disease resistance events (Doke 1983a, b;Doke and Ohashi 1988;Á dám et al 1989;Levine et al 1994;Baker and Orlandi 1995;Delledonne et al 2001;Torres et al 2006;Shang et al 2010;Torres 2010;Dubiella et al 2013). …”
Section: Early Research On the Role Of Ros In Plant Disease Resistancementioning
confidence: 99%
“…First, a cause-and-effect relationship between animal phagocytosis and the accumulation of ROS has been demonstrated (Morel et al 1991;Segal 2008). Second, ROS accumulation has been also associated and functionally linked to numerous plant disease resistance events (Doke 1983a, b;Doke and Ohashi 1988;Á dám et al 1989;Levine et al 1994;Baker and Orlandi 1995;Delledonne et al 2001;Torres et al 2006;Shang et al 2010;Torres 2010;Dubiella et al 2013). …”
Section: Early Research On the Role Of Ros In Plant Disease Resistancementioning
confidence: 99%
“…Shang et al [135] reported a differential response between the infected yellow leaf tissues and the so-called "dark green islands" (DGIs) in N. tabacum leaves systemically infected with CMV. DGIs are defined as a cluster of green leaf cells free of virus but surrounded by yellow leaf tissues where the virus is present [10].…”
Section: Plantecucumovirus Interactionsmentioning
confidence: 99%
“…In addition, a strong increase in the activity of SOD (an H 2 O 2 -generating enzyme) was observed in these virussusceptible areas that can partially account for the increased H 2 O 2 accumulation. As a consequence of the ROS accumulation in infected leaves, an increase in lipid peroxidation was produced in both leaf tissues although the cell damage was much higher in the yellow leaf tissue than in the DGIs and electrolyte leakage, indicating reduced membrane stability and integrity, showed an increase only in these susceptible tissues [135] ( Table 1). The abovementioned results support the idea that in compatible plantevirus interactions a massive oxidative stress, marked by H 2 O 2 -generation, may occur in susceptible tissues that can contribute to the onset of disease symptoms.…”
Section: Plantecucumovirus Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is a cause-and-effect relationship between animal phagocytosis and the accumulation of ROS (Morel et al, 1991). Second, ROS accumulation has been also detected in the course of several plant immunity events (Doke, 1983;Doke and Ohashi, 1988;Ádám et al, 1989;Levine et al, 1994;Baker and Orlandi, 1995;Delledonne et al, 2001;Apel and Hirt, 2004;Delledonne, 2005;Torres et al, 2006;Shang et al, 2010). Furthermore, it was experienced that the accumulated ROS can protect plants from a late infection.…”
Section: What Is Inhibiting or Killing Pathogens During The Immune Prmentioning
confidence: 99%